Practical tips for scientific goat feeding and management - Nageswara Rao, S. B.; Ramachandran, N; Chandrasekharaiah, M (Indian Farming, 2022)
Feeding alone accounts for about 70% cost of goat rearing like any other livestock enterprise and this becomes critical, if goats are reared under a stall feeding system. For successful establishment of commercial goat farms in long run, the feeding should aim to meet the nutrient requirement for different physiological stages judiciously while maintaining the feed wastage to the bare minimum at farm by following scientific feeding practices with the help of feeding devices, locally available feed resources etc. Goats respond readily to good management and proper feeding, and to ensure best results, their care should be taken like other valuable animals.